Pelvic MRI findings in relapsed prostate cancer after radical prostatectomy. Issue 1 (December 2015) - Hernandez, D.; Salas, D.; Giménez, D.; Buitrago, P.; Esquena, S.; Palou, J.; de la Torre, P.; Pernas, J.; Gich, I.; de Segura, G.; Craven-Bartle, J.; Sancho, G.
Abstract Purpose/Objective Little is known about the clinical impact of using multiparametric MRI to plan early salvage radiotherapy after radical prostatectomy. We aimed to evaluate the incidence and location of recurrence based on pelvic multiparametric MRI findings and to identify clinical variables predictive of positive imaging results. Materials and methods We defined radiological criteria of local and lymph node malignancy and reviewed records and MRI studies of 70 patients with PSA recurrence after radical prostatectomy. We performed univariate and multivariate analysis to identify any association between clinical, pathological and treatment-related variables and imaging results. Results Multiparametric MRI was positive in 33/70 patients. We found local and lymph node recurrence in 27 patients and 7 patients, respectively, with a median PSA value of 0.38 ng/ml. We found no statistically significant differences between patients with positive and negative multiparametric MRI for any variable. Shorter PSADT was associated with positive lymph nodes (median PSADT: 5.12 vs 12.70 months; p: 0.017). Conclusions Nearly half the patients had visible disease in multiparametric MRI despite low PSA. Positive lymph nodes incidence should be considered when planning salvage radiotherapy, particularly in patients with a short PSADT.